Incidence and characteristics of preeclampsia patients: a descriptive study - Putra, Ida B. A. W.; Putra, I. Wayan A.; Aryana, Made B. D.; Winata, I. Gde S. (International Journal of Research in Medical Sciences, 2024)
Background: More than 70% of maternal deaths are caused by preeclampsia and eclampsia. This study aimed to evaluate the characteristics of pregnant women with preeclampsia in the obstetrics emergency room of Prof. Dr. I. Gusti Ngoerah Gede (I.G.N.G.) Ngoerah General Hospital, Denpasar, in 2022. Methods: This study was conducted with a high level of thoroughness and detail. Data obtained include age data, gestational age, parity, employment, education, history of hypertension, history of pregnancy with preeclampsia before, blood pressure measurement results, body mass index (BMI), laboratory examination results, NST picture, complications, mode of delivery, APGAR, and birth weight. The collected data was meticulously tabulated, analyzed, and presented as tables and narratives. Results: The findings of this study are significant for the field of obstetrics and gynecology. The incidence of preeclampsia in the obstetrics emergency room of Prof. Dr. I.G.N.G. Ngoerah General Hospital reached 15.75% in 2022 with a 0% case fatality rate. The average age was 31 years. Sixty-one subjects (62.89%) were primiparous, 41 subjects (42.27%) had a history of hypertension, and 23 subjects (23.71%) had a history of pregnancy with preeclampsia. The median BMI reached 22.3 kg/m2. The mean platelet of 354 103/µl, creatinine of 0.7 mg/dl, and 93 subjects (95.88%) were positive for proteinuria. Based on the NST picture obtained, 37 (38.14%) patients had reactive non-stress test pictures. APGAR score >7 of 76 subjects (78.35%) with a median birth weight of 1,850 grams. Conclusions: This study is expected to be a reference for further research. Further research is needed to assess the relationship between demographic characteristics and the risk factors of preeclampsia.